Kegiatan Belajar Terganggu Karena Banyak Menggunakan Handphone (Studi Kasus Pada Siswa MAN 2 Model Medan dan Cara Penanganannya oleh Guru BK - Harahap, Ade Chita Putri; Azzura, Aika; Rambe, Afghan Bai Asy Ary; Ashari, Ayu; Al Mefa, Fadira; Rahmayani, Hafsah Dahni; Rezky, Sri; Atari, Nabila (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to find out whether the use of mobile phones can interfere with learning activities for students and to find out the treatment that is usually given by guidance and counseling teachers. The research method used in this study is a descriptive qualitative research method using data collection techniques, namely interview and observation techniques. The research subjects in this study were guidance and counseling teachers at MAN 2 Medan and 21 students at MAN 2 Medan. The results of the study show that the use of mobile phones can interfere with student learning activities, but on the other hand the teaching and learning process of MAN 2 Model is also somewhat assisted by technology in the form of mobile phones such as in providing material, google forms, and learning videos on certain subjects. The handling provided by the guidance and counseling teacher is to provide information services for mild cases and for severe cases the guidance and counseling teacher will call the parents of the students. Keywords: Learning Activities, Mobile